2013
DOI: 10.1017/s1047951112002235
|View full text |Cite
|
Sign up to set email alerts
|

Spinal surgery in the univentricular heart – is it viable?

Abstract: Spinal surgery in patients with Fontan circulation is a high-risk operation. These patients must be managed by a specialised team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For this reason preferable these patients must be operated in the Cottrell or in the Jackson table, in which the patient is fastened and the abdomen, and inferior cava vein system, is not compressed [5]. The postoperative complications are frequent being worst the respiratory complications considering that almost all these children are diagnosed of restrictive disorders furthermore their heart disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason preferable these patients must be operated in the Cottrell or in the Jackson table, in which the patient is fastened and the abdomen, and inferior cava vein system, is not compressed [5]. The postoperative complications are frequent being worst the respiratory complications considering that almost all these children are diagnosed of restrictive disorders furthermore their heart disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have reported anecdotal experiences with the perioperative care of this population during PSF (Table 1) [15][16][17][18][19][20]. The Fontan operation, while providing a corrective procedure for complex cardiac malformations characterized by single ventricle anatomy, leaves the patient's CO dependent on passive PBF.…”
Section: ]mentioning
confidence: 99%
“…Spinal surgery in patients with CHD has become safer with time, however the risk of perioperative complications remains high 17–21 . This risk is greatest in patients with single ventricle physiology and requires multidisciplinary care and preparation for adverse perioperative events 21–27 . Our institution recently reviewed 78 patients with CHD undergoing scoliosis surgery and found patients with cyanotic single ventricle physiology had the highest risk for adverse perioperative events 21 .…”
mentioning
confidence: 99%
“…[17][18][19][20][21] This risk is greatest in patients with single ventricle physiology and requires multidisciplinary care and preparation for adverse perioperative events. [21][22][23][24][25][26][27] Our institution recently reviewed 78 patients with CHD undergoing scoliosis surgery and found patients with cyanotic single ventricle physiology had the highest risk for adverse perioperative events. 21 Our single ventricle physiology cohort has grown since this research and an earlier review of Fontan patients.…”
mentioning
confidence: 99%